2014
DOI: 10.7860/jcdr/2014/9114.4609
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology and Prognostic Indices of Carcinoma Breast with Special Reference to p53 Marker

Abstract: Introduction: Cancer of the breast is one of the commonest carcinomas in women, both in western world and in India. The high frequency of breast cancer in women has prompted an intensive study of possible modifiable risk factors (clinical parameters, morphological typing, and biological markers) for assessment of prognosis, prevention strategies, and treatment modalities. p53 is one of the most significant prognostic markers for breast carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The p53 protein is a DNA‐binding protein localized to the nucleus, which functions primarily by controlling the transcription of several other genes responsible for cell growth and also mediates cell cycle arrest and apoptosis (27) . Previous data found that p53 overexpressing tumors demonstrate aggressive characteristics, including larger size, higher grade, and necrosis in comparison with p53 negative cases (28) . On the other hand, ve is one of the main pharmacokinetic parameters suggesting EES volume fraction.…”
Section: Discussionmentioning
confidence: 91%
“…The p53 protein is a DNA‐binding protein localized to the nucleus, which functions primarily by controlling the transcription of several other genes responsible for cell growth and also mediates cell cycle arrest and apoptosis (27) . Previous data found that p53 overexpressing tumors demonstrate aggressive characteristics, including larger size, higher grade, and necrosis in comparison with p53 negative cases (28) . On the other hand, ve is one of the main pharmacokinetic parameters suggesting EES volume fraction.…”
Section: Discussionmentioning
confidence: 91%
“…However, Radha et al reported an equivocal P53 status in both the positive and negative cases of lymph node metastases in immunohistochemistry results. 21 In this study, the odds ratio of P53 positivity were 0.97 times (95% CI, 0.59–1.57, P = 0.892) in people with positive lymph node status. In other words, no correlations were possible between P53 and axillary lymph node metastases.…”
Section: Discussionmentioning
confidence: 51%
“…Percentage of positive cells varied from <10% to >50% with weak, intermediate and strong intensity. In many other studies by Arora et al, [1] Patnayak et al, [6] Sekar et al, [13] Radha et al, [14] Neharika et al [10] p53 positivity was observed in 61.5%, 69.2%, 71.6%, 22%, 47.4% cases respectively. Variability in the p53 expression may be attributed to the diverse range of procedures and reagents used by different investigators.…”
Section: P53 Scoringmentioning
confidence: 82%